2014
DOI: 10.1136/bmj.g6652
|View full text |Cite
|
Sign up to set email alerts
|

The attributable mortality of delirium in critically ill patients: prospective cohort study

Abstract: Objective To determine the attributable mortality caused by delirium in critically ill patients.Design Prospective cohort study.Setting 32 mixed bed intensive care unit in the Netherlands, January 2011 to July 2013.Participants 1112 consecutive adults admitted to an intensive care unit for a minimum of 24 hours.Exposures Trained observers evaluated delirium daily using a validated protocol. Logistic regression and competing risks survival analyses were used to adjust for baseline variables and a marginal struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
107
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(127 citation statements)
references
References 65 publications
5
107
0
4
Order By: Relevance
“…The following variables for entry into the model were selected a priori, on the basis of published studies and clinical importance 6,8,[19][20][21] : age, APACHE II score, use of antipsychotic before ICU admission (a potential marker of delirium before transfer to the ICU), duration of mechanical ventilation, exposure to benzodiazepines (expressed in midazolam equivalents), agitation (defined as a score > 4 on the Riker Sedation-Agitation Scale [SAS]), 22 use of daily sedation interruption, use of a delirium screening tool, and application of physical restraints. Patients with a documented history of schizophrenia who were treated with antipsychotics were excluded from the multivariable analysis.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…The following variables for entry into the model were selected a priori, on the basis of published studies and clinical importance 6,8,[19][20][21] : age, APACHE II score, use of antipsychotic before ICU admission (a potential marker of delirium before transfer to the ICU), duration of mechanical ventilation, exposure to benzodiazepines (expressed in midazolam equivalents), agitation (defined as a score > 4 on the Riker Sedation-Agitation Scale [SAS]), 22 use of daily sedation interruption, use of a delirium screening tool, and application of physical restraints. Patients with a documented history of schizophrenia who were treated with antipsychotics were excluded from the multivariable analysis.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…[1][2][3][4][5][6] Professional society guidelines 7,8 recommend the routine use of screening tools specifically designed for detecting delirium in critically ill patients (e.g., the Confusion Assessment Method for the Intensive Care Unit [CAM-ICU] 9 and the Intensive Care Delirium Screening Checklist [ICDSC] 10 ). However, international surveys and observational studies have indicated that delirium screening tools are not widely incorporated into critical care practice, [11][12][13][14][15][16] which represents a missed opportunity to detect the syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Hippocrates associated it firmly with oncoming death (Adamis et al 2007); delirium remains closely associated with mortality (see for example Klouwenberg et al 2014). The two figures I describe -friendly and unfriendly -are one frame through which to understand this world.…”
Section: Resultsmentioning
confidence: 99%
“…Mortalite/Morbidite: Deliryum gelişimi, yoğun bakımda yatan ağır hastalarda mortalite oranlarını en az %10 artırır (13). Hastanede yatış sırasında deliryum gelişen yaşlı hastaların taburcu olduktan sonra izlendiği bir çalışmada 12 ay içinde mortalite oranı %63,3 olarak bulunmuştur.…”
Section: Klinik Ve Araştırma Etkileriunclassified